A Pilot Study of a Novel Fixation Technique for Fixation of Comminuted Patellar Fractures: Arthroscopic-Controlled Reduction and Circular External Fixation - Neyisci, Cagri; Erdem, Yusuf; Kilic, Erden; Arsenishvili, Arsen; Kürklü, Mustafa (The Journal of Knee Surgery, 2020)
Patella fractures represent for 0.5 to 1.5% of all bony injuries in adults. Open reduction and the modified tension-band technique is the most common surgical technique used for patellar fractures. The purpose of this study is to present the outcomes of 26 comminuted patellar fractures treated with circular external fixator (CEF) under arthroscopic control and discuss its potential advantages over conventional surgical methods. This retrospective study included 26 patients who had closed comminuted patellar fractures and treated by CEF under arthroscopic control between January 2002 and March 2016. All patients treated with this technique were involved to the study as a consecutive series. Patients with noncomminuted transverse fractures were excluded, because they were treated with a different technique. Of the 26 patients 22 were male, 4 were female with the mean age of 33.5 years (range, 16–56 years). Patients were followed for 20 to 28 months (mean, 22 months). The mean time to union and the duration of fixation with the CEF ring was 12 weeks (range, 6–15 weeks). The mean Lysholm's score was 45 (range, 35–58) at the 10th postoperative day, which increased to 51 (range, 40–68) at the end of the first postoperative month and increased to 95 (range, 90–100) 1 month after CEF ring removal. Minor pin tract infection by pin-skin irritation was observed in nine patients. In one patient, refracture occurred due to a fall 19 days after CEF removal. CEF appears to be a safe and effective treatment for comminuted patellar fractures with a high union rate and minimal complications. It is safe and effective, as it allows short hospital stay and avoids a second surgery for removal of the instrument. Early rehabilitation with full weight-bearing promotes rapid recovery and quick return to work. Patients do not have a large unaesthetic scar on the anterior of the knee.
Keywords: comminuted; patella fractures; external fixator; arthroscopy